Music Therapy to Reduce Pain Intensity in Post Fracture Surgery Patients : Systematic Review - Nuriya Nuriya; Galih Noor Alivian; Agis Taufik; Saryono Saryono (International Journal of Biomedical Nursing Review, 2023)
Introduction: Fracture is a loss of continuity of bone, either total or partial, is usually caused by trauma, which is characterized by a history of trauma fracture, pain and swelling in the broken bones, deformity, musculoskeletal dysfunction, breaking the continuity of the bone, and neurovascular disorders. Purpose: The purpose of this study is to identify the effectiveness of music therapy in reducing pain scale on postoperative patients with fracture so it can be added to the understanding of nursing in caring for patient with postoperative fracture pain. Method: This systematic review was carried out according to the PICO model. Keywords in the search for evidence based in this literature review include: “pain scale”, “music therapy”, “postoperative”, “fracture”. Database searches or databases were carried out in December 2022 using Google Scholar, PubMed, Neliti, and Genius. Result: Music therapy applied to the patient with postoperative fracture can reduce the pain scale level. Discussion: One of the treatments from the nursing field that can help reduce pain scale level in patients with postoperative fracture pain is music therapy. Conclusion: Based on the analysis that has been done by the author, it can be concluded that music therapy helps to reduce the pain in postoperative fracture by the activation of brain stem reticulum because a signal to inhibit pain is sent to the spinal cord, and this causes the gateway to close.